(untitled) (Journal of Tourism & Adventure, 2018)
Tourism is forefront of many economy but come with negative externalities resulting in diminished environmental quality. In place of these mass tourism practices, different alternative forms of tourism are practiced with aim of enhancing positive externalities while keeping check and balance to negative externalities. Ecotourism is one such approach which is often highlighted as one of the most effective tool to reconcile the conservation and development aspiration. Ecotourism in its different localized version and their impacts on environment are studied in Nepal. Despite this, ecotourism potential of protected areas is less explored dimension in ecotourism studies. This holds true for the eastern region of the lowland Nepal. Location of destination, features of that destination along with the facilities and uniqueness offered by the place is different which are vital in defining the ecotourism potential of different locations. The study forms the basis for promotion of ecotourism in an area. This paper aims to explore the ecotourism potential of Koshi Tappu Wildlife Reserve. There are different tools and approach used to assess the ecotourism potential. This paper contains information collected from field observation, scheduled interview and key informant interview. Wild Water Buffalo, migratory birds along with the presence of other wildlife species make a place attractive destination for ecotourism. Satisfaction shown by the respondents for food, accommodation and hospitality offered adds value to the ecotourism potential. Areas with high scenic and cultural attraction in the vicinity of the park can be considered as positive additionally to attract tourist with diverse interest. As it is considered mandatory to include the component of education and interpretation to qualify as ecotourism, development and execution of the curriculum are essential. Beside this, exploration and marketing of other potential destination and enabling the local communities are equally vital.